PENDAMPINGAN MENGUBAH WARNA RGB MENJADI WARNA LAINNYA UNTUK KEGIATAN FINGER PAINTING PADA ANAK USIA DINI - Ferdian Utama (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2022)
Finger painting is one of the most popular art activities among early childhood. In this context, understanding the concept of color is very important. This research aims to develop assistance that helps early childhood children change colors in finger painting using the RGB (Red, Green, Blue) color concept into other colors. The results of the service show that this assistance is effective in improving children's understanding of color and encouraging richer creative expression. Children who used this assistance showed an increase in understanding of color mixtures and were able to create more diverse finger painting artworks. This research also has practical implications in the context of early childhood art education and development. Although this activity has some limitations, the results provide a basis for further development in the use of mentoring in early childhood art contexts. It is hoped that this research can make a positive contribution in enriching young children's art experiences and facilitating a better understanding of the world of color.